Laser balloon in pulmonary vein isolation for atrial fibrillation: current status and future prospects. (2nd November 2021) - Tohoku, Shota; Bordignon, Stefano; Bologna, Fabrizio; Chen, Shaojie; Urbanek, Lukas; Operhalski, Felix; Chun, KR Julian; Schmidt, Boris
ABSTRACT: Introduction: Visually guided laser balloon (LB) catheter has been an established modality dedicated for pulmonary vein (PV) isolation in patients with atrial fibrillation. The newly updated version of this novel device has technically evolved recent years. Areas covered: This review will summarize the contemporary technical evolution of LB catheter. Available efficacy outcomes and the historical change of ablation style will be evaluated. Furthermore, the future perspectives for clinical practice are discussed. Expert commentary: The initial LB ablation system provided comparable clinical results in PV isolation with other technologies, but with a unique strategical concept enabling the direct visualization of the tissue to cauterize. With multigenerational development, the LB catheter has been equipped with more compliant balloon for favorable PV occlusion and a robotically motor driven continuous ablation mode (RAPID mode). These technical innovations changed the concept of the ablation strategy using LB catheter as 'point-by-point' into 'single-shot' fashion. The remaining tasks are further improvements such as equipping with real-time recording system of intracardiac electrogram, durable structured balloon and the instrument for visualizing the cauterization area in a 360-degree panoramic view, which includes potential possibilities to develop this novel device to the more optimal device for PV isolation.